2011
DOI: 10.1111/j.1469-8749.2011.03953.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb function and deformity in cerebral palsy: a review of classification systems

Abstract: MACS Manual Ability Classification SystemAIM To review classification systems for the upper limb in children with cerebral palsy (CP), and evaluate their validity, reliability, and clinical utility to make recommendations for clinical practice and future research.METHOD We comprehensively searched electronic databases to identify upper limb classification tools and associated evidence of psychometric testing. Two independent reviewers assessed the quality of the psychometric studies, and rated the clinical uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
(220 reference statements)
2
22
0
2
Order By: Relevance
“…MHC evaluates the 3 categories of hand function (reaching, grasping and manipulating objects) and represents the best capacity of each hand. In a previous study, MHC was recommended as a reliable tool to classify upper limb function in children with CP 3. In the present study, we identified a strong relation between MHC and MACS in children with bilateral CP.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…MHC evaluates the 3 categories of hand function (reaching, grasping and manipulating objects) and represents the best capacity of each hand. In a previous study, MHC was recommended as a reliable tool to classify upper limb function in children with CP 3. In the present study, we identified a strong relation between MHC and MACS in children with bilateral CP.…”
Section: Discussionsupporting
confidence: 65%
“…The Gross Motor Function Classification System (GMFCS) is widely used to assess the gross motor function in children with CP, and the Manual Ability Classification System (MACS) was developed to evaluate a child's typical manual performance in daily life 1,2. GMFCS is now universally accepted as a valid and reliable means of classifying gross motor function in children with CP 3. However, MACS has recently gained attention as a valid and reliable classification system for upper extremity functions in children with CP aged 4 to 18 years 1,4.…”
Section: Introductionmentioning
confidence: 99%
“…In line with a previous study of McConnell et al, 81 the MACS was found to be the tool with most published evidence. It shows moderate positive levels of evidence for interrater reliability (when only considering comparisons between therapists) and test-retest reliability.…”
Section: Reliabilitysupporting
confidence: 89%
“…In comparison with previous reviews, [3][4][5]8,80,81 the current article covered a broader age range and several diagnoses. This ensured a comprehensive overview of the evidence of assessment tools used in clinical everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…The children instead of tapping at some touchscreen, must move their arms and point at a certain spot in space. According to the Manual Ability Classification System (MACS) [16] scale, our games are suitable for CP patients of level II and III. Note here that we are currently developing games that target pinch and supination rehabilitation.…”
Section: Proposed Rehabilitative Gamesmentioning
confidence: 99%